CUTANEOUS AND PULMONARY INFECTION BY MYCOBACTERIUM AFRICANUM - Francisco, Telma; Cunha, Daniela; Vieira, Raquel; Afonso, Ana; Brito, Maria João (Journal of the Portuguese Society of Dermatology and Venereology, 2013)
Cutaneous tuberculosis is an uncommon disease, accounting for 1.5% of all types of tuberculosis. In pulmonary and cutaneous disease, infections caused by Mycobacterium africanum and Mycobacterium tuberculosis can be clinically indistinguishable. A six-year-old boy from Guinea-Bissau was hospitalized due to a right pre-auricular ulcer with two-year evolution and regional lymphadenopathy. Tuberculinic test was positive and the thoracic radiography showed a hypotransparent node on the right lower pulmonary lobe, with solid characteristics in CT scan. Skin ulcer and lymphadenopathy biopsies revealed lymphocytic infiltrate with a granulomatous reaction; the culture and PCR confirmed Mycobacterium africanum infection. Antibacillary treatment was supplied for six months, leading to significant reduction of the lesion. In developed countries it’s important to remind the several forms of cutaneous tuberculosis, which can present solely or in association with other forms of infection. In patients from endemic areas, a positive tuberculinic test should rise the suspicion of this entity. KEY-WORDS – Tuberculosis, cutaneous; Tuberculosis, pulmonary; Mycobacterium infections; Child.